Visual search strategies and executive functioning in South African sailors - Walker, C. N. (2015)
Background: The ability to locate and identify relevant visual information is essential for skilful behaviour as well as to make performance-related decisions. Decision-making is a subcomponent of executive functioning and involves choosing between two or more possible solutions. Visual search behaviour is a dynamic self-organised perceptual skill that is based on the interaction between constraints imposed by the task, the environment, and the individual characteristics of the athlete (Williams, Ward, Smeeton, & Allen, 2004). Technologies-based feedback such as visual search behaviour may provide relevant information to enhance skill acquisition and sport performance in sailors and, as such, its usefulness to sport scientists, coaches and athletes in training is beneficial. Despite recognizing the importance of the visual search behaviour in sailing little research has been done. To the researcher?s knowledge, no research has been done on describing South African expert sailors? visual search behaviour and executive functions. Aim: This investigation set out to determine the i) visual search strategies in two simulated events and ii) executive functions, as an indicator of decision-making skills, of expert South African sailors. Methods: The investigation followed an observational method descriptive design, where National level South African sailors (n = 61), with an average age of 26 years (SD = 8.88) and professional sailing years of 14 (SD = 7.54), volunteered to participate in the investigation. Visual search strategies of the sailors were determined using a mobile eye tracker during two sailing simulations (computer, n = 24; and radio controlled boats; n = 22). In order to determine the executive functioning (EF) capabilities of the sailors (n = 15), a battery of valid EF tests was compiled comprising the Montreal Cognitive Assessment (MoCA), Wisconsin Card Sorting Test (WCST), Trail Making Test (TMT part A and B), and adapted Stroop Task. Results: All the sailors fixated considerably more on their own boat than any other fixation location; however the top ranking and successful groups performed fewer fixations (d between 0.29 - 0.72) of longer duration (d between 0.05 - 0.59) compared to their counterparts in both simulation studies. The helms performed better on the TMT and Stroop task, while the crews achieved better on the WCST (d = 0.92 - 1.62). Conclusion: By describing sailors? visual search strategies, we know what they consider relevant information which contributes to better decision-making and subsequent skilled performance. This may help coaches to enhance sailing performance in less experienced sailors by directing their visual search behaviour to these relevant cues, specifically to look more at their own boat in order to maintain speed and improve performance. The executive functioning skills tell us that successful sailors require the skill to shift their attention and solve problems based on the constantly evolving environment.